The structure, diversity and somatic production of the fish community in an estuarine coastal lagoon, Ria de Aveiro (Portugal) - Pombo, L. (2007)
The present study aims to determine biological fish production of a lagoon and relate this to the commercial fisheries yield. The fish community of an estuarine lagoon in the west coast of Portugal was sampled between November 1998 and November 2000 to estimate the production ecology of the community, including somatic production, population size, species richness, species diversity, and biomass. Using the Allen curve method of determination, the total annual fish production of all fish species in the lagoon was calculated at 90.3 tonnes or 2.1 g m−2 year−1 in the first year and 106.7 tonnes or 2.5 g m−2 year−1 in the second year. The marine seasonal migrant species, sardine, Sardina pilchardus, which colonises the lagoon during the juvenile period of its life stages, produced more than 35 tonnes in each year and accounted for >39 and >33%, in the first and second year respectively, of the total fish production in this lagoon. Sardine was numerically more abundant (18,217 specimens) but due to their small size contributed only 13% to the total biomass. Sardine was thus the most important fish species in terms of the consumption and production processes of the whole fish community in this system. Commercial fisheries’ records indicate that approximately 300 tonnes per annum of fish are taken from the lagoon, which corresponds to three times more than the estimated production in the lagoon. Thus, if it exists, the sustainability of the fishery appears to depend on the immigration of fish from the adjacent coastal area and it is questioned whether the fishery is sustainable in the long-term. The findings indicate that careful and effective management of the lagoon is required to ensure a long-term healthy aquatic environment and sustainable catches in the future.